Evaluation of Genetic Diversity of Iranian Spring Wheat Cultivars under Salinity Stress at the Seedling Stage using Multivariate Statistical Methods - Ronak Talebi Qormik; Hadi Alipour; Reza Darvishzadeh (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: In arid and semi-arid regions, biotic and abiotic stresses can directly or indirectly lead to restrictions and decreased growth of different plants. In these areas, salinity stress is one of the major challenges facing agriculture and crop production that causes huge damage to crop yields annually. The amount of salinity in the soil results in plant growth limitation, and increased soil salinity disrupts water and essential nutrient absorption for the plant and reduces plant growth, which can then lead to plant death. Reduced root growth and development, decreased nutrient absorption, increased likelihood of allergies to diseases and pests, decreased yield, and final product quality (e.g., nutrient deficiency), and increased toxic elements, are among the negative effects of salinity on plants. Various factors are involved in the creation of salinity, the most important of which can be climate change, source rock weathering, improper irrigation, drought, excessive consumption of fertilizers, and reduced seawater levels. Following climate change, these damages are on the rise every year. Due to the increase in population growth, demand for food production is increasing day by day. Wheat is known as the major grain in the supply of nutritional needs in the world, hence its sustainable production is of paramount importance. Salinity is recognized as an important factor in reducing wheat yield, and it may increase the accumulation of harmful salts in the plant tissue, which can lead to physiological damage and decreased plant growth. The effects of soil salinity vary depending on the amount of salinity, the type of salinity, and the type of wheat. One way to prevent the negative effects of salinity is to use salinity-resistant wheat cultivars. The range of diversity in relation to salt stress tolerance in different plants, especially the wheat plant, depends on various factors such as plant genotype, duration of stress, and plant growth stage. The seedling stage in wheat is one of the important stages regarding tolerance to salt stress. This study aims to investigate the response of spring wheat cultivars in the seedling stage to salinity stress. Methods: In the present study, the reaction of 64 Iranian spring wheat genotypes at the seedling stage under normal conditions and 12 dS/m salinity stress was investigated in two replications in a simple lattice design at the research greenhouse of the Faculty of Agriculture, Urmia University in 2021-2022. In this study, in the four-leaf stage, salinity stress was applied gradually for two days. The measured traits were chlorophyll (SPAD), canopy temperature, shoot length (SL), root length (RL), seedling length (PL), shoot potassium content (KS) ), root potassium content (KR), shoot sodium content (NaS), root sodium content (NaR), shoot potassium to sodium ratio (KNaS), root potassium to sodium ratio (KNaR), root volume (RV), leaf area index (LAI), radicle fresh weight (FWR), radicle dry weight (DWR), relative leaf water content (RWC), shoot fresh weight (FWS), shoot dry weight (DWS), seedling fresh weight (FWP), weight dry matter of seedlings (DWP). The data of the studied traits were obtained in a random complete block design. PROC GLM was used for the analysis of variance (ANOVA) in SAS 9.4 software. The correlation was examined using PROC CORR and decomposition into factors using PROC FACTOR. The figures were grouped using the gplots software package and the biplot diagram was drawn with the factoextra software package in the R 4.1 environment. The MANOVA statement in PROC GLM was used in SAS 9.4 software for multivariate variance analysis. Results: Based on the results of ANOVA, statistically significant differences were observed between the tested cultivars based on the traits studied in the seedling stage, including FWP, DWP, FWR, DWR, FWS, RWS, and (PL). In both normal and salt stress conditions, DWP showed the most significant correlation with FWP, DWS, and DWR. Under the salinity stress conditions, FWS was significantly correlated with DWS, FWP, and DWP. Based on factor analysis, the studied traits in both normal and salinity stress conditions were grouped into seven factors, which explained 77.93% and 76.44% of the total changes in normal and salinity stress conditions, respectively. Using cluster analysis, cultivars under both normal and salt stress conditions were grouped into three clusters. Conclusion: Based on the biplot results of factor analysis and cluster analysis, Maron, Darya, Shiroodi, Moghan 3, Darab 2, Roshan, Pishgam, and Pishtaz cultivars are introduced as favorable cultivars. Chamran, Bam, Alborz, and Maroodasht cultivars are categorized as unfavorable cultivars that can be used in further wheat breeding programs.